Characteristics of auditory processing disorder in primary school-aged children - Ferguson, Melanie A. (2014)
The aims of this research were to identify and compare auditory processing, speech intelligibility, cognitive, listening, language and communication abilities in (i) typically developing, mainstream school (MS) children (n = 122) for direct comparison with (ii) children presenting to clinical services with auditory processing disorder (APD) (n = 19) or specific language impairment (SLI) (n = 22), and in (iii) a large population sample (n = 1469) who were categorised by their functional listening and communication abilities according to parental report rather than clinical diagnosis. All had normal hearing sensitivity.